P-252 Movement wide change and organisational institutionalism. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Hodges, Emma; Read, Sue
Abstract : Hospices are being challenged by changing demographics. Originating from a response to cancer, hospices have struggled to significantly shift their narrative. This abstract relates to doctoral research exploring hospices' response to dementia from an organisational theoretical lens. The research highlighted a model of institutional change (Greenwood, Suddaby & Hinings, 2002) which can be applied, beyond dementia, to the challenges hospices currently face. The model identifies stages of institutional change that potentially take an institutionalised organisational field (e.g. hospices) from their existing narrative through 'de-institutionalisation' to being 're-institutionalised' with a new, compelling narrative. The stages in-between are critical in creating the confidence for organisations to introduce significant change. The research highlights that in response to dementia (and other non-malignant diseases) key stages of institutional change have not taken place – in particular 'technical viability' (Greenwood, Suddaby & Hinings, 2002; Hodges & Read, 2018). Technical viability is what moves thinking from an idea to a fully formed argument that gains moral and practical legitimacy. A case study on institutional change by Greenwood, Suddaby & Hinings (2002) highlighted a key ingredient being organisational failure. Hospices have not, up until now, failed. The imperative for change has never been greater not only are the changing demographics challenging hospices so are the economic conditions. Whatever the future holds for hospices, the theoretical lens of organisational institutionalism adds useful concepts that would help practically. The research in relation to dementia concludes: There needs to be a national conversation on the future of hospice care and Hospice UK are doing this; There needs to be a review, using institutional change models as to why other 'external jolts' haven't created a significant movement wide shift and; There needs to be training on institutional change including understanding the social context in which each hospice operates, being part of a movement, and also the essential need for the technical viability of any proposed models.